Kualitas Fungi Mikoriza Arbuskula yang Diproduksi dengan Teknik Fortifikasi Nutrisi Berbeda terhadap Peningkatan Produktivitas Alfafa (Medicago sativa L.): Quality of Arbuscular Mycorrhizal Fungi Produced with Different Nutritional Fortification Techniques for Increased Productivity Alfalfa (Medicago sativa L.) - Ika Jenri Ramadayanti; Iwan Prihantoro; Panca Dewi Karti (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2023)
This study aimed to evaluate the quality of Arbuscular mycorrhizal fungi (AMF) produced by different nutrient fortification techniques in increasing the adaptation and productivity of alfalfa (Medicago sativa L.) at the greenhouse scale. The research design was a completely randomized design (CRD) with 5 treatments and 10 replications. The treatment based on different types of AMF product, including alfalfa without AMF as control (P0), superior AMF (P1), and three types of AMF products from the Agrostology Laboratory, Faculty of Animal Science IPB: AMF1 (P2), AMF2 (P3), and AMF3 (P4). The control treatment was given a 100% recommended fertilizer dose while the AMF treated plants were given a 50% recommended fertilizer dose. The results showed that all AMF products produced the same effectiveness for plant morphological variables. The superior AMF product, AMF2, and AMF3 gave the better response to AMF colonization parameters and dry weight of alfalfa plants than the control and AMF1 product. It was concluded that AMF products with different nutrient fortification techniques were effective in symbiosis and increase the adaptation and productivity of alfalfa compared to control. The quality of AMF produced by different nutrient fortification techniques had the same performance as superior AMF. Key words: alfalfa, arbuscular mycorrhizal fungi, nutrient fortification